Effect of Dasapaka Bala Taila Yonipooranam in Atrophic Vaginitis - A Case Report (International Journal of Ayurveda and Pharma Research, 2023)
Atrophic vaginitis is a common condition that occurs in post menopause due to the deficiency of estrogen. The condition Atrophic vaginitis is defined as atrophy of the vaginal epithelium due to decreased estrogen levels. This common menopausal condition which is often underreported and under diagnosed is caused by estrogen related changes to the vaginal epithelium and can adversely affect quality of life. Atrophic vaginitis is a common condition in postmenopausal women experience due to estrogen deficiency that causes involution of the vaginal tissue, leading to vaginal dryness, burning sensation in vagina and dyspareunia, the atrophy of the vulvovaginal structures occurs due to estrogen deficiency. Among them Sushka yoniroga can be most suitably correlated with Atrophic vaginitis. The management principle of Atrophic vaginitis includes Vathika yoniroga chikitsa, along with Sthanika chikitsa. Treatment mainly aims at Vatapittasamana, Brimhana, Balya and natural supplementation of estrogen containing drugs. Sthanika chikitsa like Yonipooranam, Pichu dharanam, etc can be done in Atrophic vaginitis. Sthanika chikitsa which is of prime importance in the management of Streeroga facilitates absorption of drugs through the vagina as the walls and adjacent tissues are highly vascular, where the medicines are administered intra vaginally. In the present case, Yonipoorana as Sthanika chikitsa as tried. A 54 year old lady was presented with complaints of burning sensation in vagina and pain during sexual intercourse. The vaginal examination was painful and the walls are found inflamed, she was diagnosed with Atrophic vaginitis. She was sent to cytological screening. The reports revealed high grade parabasal cells and low grade superficial cells. The maturation index was found 60/25/5 vaginal pH was 5.3. Pap smear was done which was negative for intraepithelial lesion or malignancy. Dasapaka Bala tailam was administered intravaginally for 7 days in 3 consecutive months. During follow up she was relieved from the symptoms like burning sensation in vagina and pain during sexual intercourse. From this case report, it shows that Yonipoorana with Dasapaka Bala tailam is effective for the management of Atrophic vaginitis.